2023
DOI: 10.3390/w15193472
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH, COD, and HRT on the Performance of Microbial Fuel Cell Using Synthetic Dairy Wastewater

Aritro Banerjee,
Rajnish Kaur Calay,
Subhashis Das

Abstract: Microbial fuel cells (MFC) are emerging technologies that can produce electricity while treating wastewater. A series of tests were carried out to evaluate the efficiency of this technology for treating dairy wastewater (DWW). The experiments used Shewanella baltica as an exoelectrogen in a small single MFC to treat simulated DWW. The impacts of various operational factors, specifically pH, hydraulic retention time (HRT), and chemical oxygen demand (COD) in the influent to the anode chamber, were investigated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The pH values increased from the border of slightly acidic (3.874) to slightly alkaline (9.311 ± 0.417), with an optimal pH value shown on day 14 of 7.141 ± 0.134, Figure 4a. The literature review mentioned that bacteria require a neutral pH for adequate growth, while the reduction process that occurs in the cathode chamber tends to have an alkaline pH [42,43]. The standardization of the pH value is of utmost importance because microbes need an adequate value for their growth and generation of electrons [44].…”
Section: Results and Analysismentioning
confidence: 99%
“…The pH values increased from the border of slightly acidic (3.874) to slightly alkaline (9.311 ± 0.417), with an optimal pH value shown on day 14 of 7.141 ± 0.134, Figure 4a. The literature review mentioned that bacteria require a neutral pH for adequate growth, while the reduction process that occurs in the cathode chamber tends to have an alkaline pH [42,43]. The standardization of the pH value is of utmost importance because microbes need an adequate value for their growth and generation of electrons [44].…”
Section: Results and Analysismentioning
confidence: 99%
“…Freshwater resources directly available to humans account for only 2.7% of the global water resources, with the remainder accounting for salty or brackish water bodies. The problem is aggravated by the fact that freshwater resources are extremely uneven, causing serious shortages in many countries and regions [78][79][80]. The unitization of solar energy for the evaporation of seawater or sewage to improve the water quality has been proven to be an environmentally friendly and sustainable water treatment technology.…”
Section: Fibrous Microfluidic Systems Current State Of Researchmentioning
confidence: 99%
“…Therefore, from Equation (44), it stands to reason that there exists an optimum pH for MFC/MMFC operation. Consequently, Banerjee et al (2023) [164] have reported that the best performance of the MFC occurs when the pH of the aqueous solution at the anode is 8, in the presence of a chemical oxygen demand (COD) of 632 mg/L, with the maximum power density and microbial electrochemical efficiency being 138 mW/m 2 and 71%, respectively. In the literature, the surface charge density has been linked to the number density of ionizable surface groups, where direct proportionality is applicable [165].…”
Section: Ph Effectmentioning
confidence: 99%
“…In recent literature, there has been notable attention directed towards various categories of wastewater within the context of MFCs. An example of this focus is evident in the investigation carried out by Banerjee et al (Banerjee et al, 2023), where an MFC system was employed for the treatment of dairy wastewater. The study noted that the MFC exhibited a maximum power density of 138 mW/m 2 and achieved a chemical oxygen demand (COD) removal rate of 71%, highlighting its effectiveness in wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%